Technical Guidance for Student Creativity and Achievement Program - Hamdani; Dona Fitriawan; Halini; Agung Hartoyo; R, Zubaidah; Revi Lestari Pasaribu; Dian Ahmad BS; Ade Mirza; Edy Yusmin; Asep Nursangaji (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The purpose of the student creativity program in general is to prepare future-oriented student resources and forged with higher education transformation so that they become superior, competitive, adaptive, flexible, productive, competitive graduates with Pancasila character, and guide students to become individuals who know and obey the rules, creative and innovative, as well as objective and cooperative in building intellectual diversity. While the objectives of the Student Achievement Program are: 1) giving awards to students who have achieved high achievements; 2) motivating students to carry out curricular, co-curricular, and extra-curricular activities as a vehicle for synergizing student hard skills and soft skills; 3) encouraging universities to develop a campus life climate that can facilitate students to achieve proud achievements on an ongoing basis; 4) Student entrepreneurship; and 5) MBKM activities in higher education. The method of delivering the material in the zoom meeting and offline, accompanied directly by selected expert presenters who are able to provide motivation and strategies and often participate in the intended achievement event in the FKIP Hall, Classroom, and other rooms that are useful in implementing activities that are planned to be carried out continuously or sustainably between April and December 2023. The activities are in the form of continuous technical guidance periodically until students are proficient in uploading activity websites, making implementation proposals, and creating achievement and entrepreneurial ideas. The data collection technique is observation, interview, and documentation. With data collection tools in the form of observation sheets, interviews, and documentation sheets. The target audience is students and lecturers, especially the mathematics education study program at FKIP Tanjungpura University. With the results obtained are: 1) many students are ready to make a team of service implementers starting from the preparation of proposals to the hope that the product will be accepted by the ministry and other institutions that oversee it; 2) students play an active role in participating in competitions or student achievement activities and compete starting from the institutional, regional, national, and international levels. The product of the service activity is in the form of a Student Creativity Program (PKM) proposal and empirical evidence of students participating in outstanding student activities then articles made and then published in the National Journal of Community Service.